Sterile Seroma Resulting from Multilevel XLIF Procedure as Possible Adverse Effect of Prophylactic Vancomycin Powder: A Case Report - Youssef, Jim A.; Orndorff, Douglas G.; Scott, Morgan A.; Ebner, Rachel E.; Knewitz, Allison P. (Evidence-Based Spine-Care Journal, 2014)
Study Design Case report.Objective The objective of this study was to present the unusual case of a 59-year-old woman with a reoccurring sterile postoperative seroma.Methods A patient was observed postoperatively for any complications or adverse side effects resulting from an initial multilevel anterior/posterior lumbar fusion surgery where 2 g (1 g combined with the bone graft used for posterolateral fusion and 1 g placed in the soft tissues) of prophylactic vancomycin powder was placed within the soft tissues posteriorly before wound closure. The patient's progress was monitored through 6 months following the initial procedure. Six weeks postoperatively, the patient sustained a fall and had increased pain. Magnetic resonance imaging, computed tomography, and X-rays demonstrated a displaced sacral fracture, a large epidural fluid collection, and severe compression of the thecal sac at the lumbar operative sites (L3–5).Results On the basis of the aforementioned imaging studies and the patient's progressive neurologic deficit, it was apparent at the 6-week follow-up that emergent surgical intervention was necessary. Drainage and examination of an epidural fluid collection along with treatment of a displaced sacral fracture (S1–S2) were performed. The patient had an uneventful postoperative course with resolution of her back pain and neurologic deficit; however, recurrence of the epidural fluid collection requiring serial aspirations confounded the patients' clinical presentation.Conclusions With the recurrent nature of the seroma being unusual, the cause of the fluid collection and formation is undetermined. With lack of bone morphogenetic protein usage, and few confounding variables accountable, an acute allergic response to topical vancomycin powder is a possible etiology. Analysis with larger patient populations comparing postoperative adverse effects of prophylactic vancomycin powder is recommended.
Keywords: vanomycin; seroma; lumbar fusion